So, What Am I Supposed to Do? A Multilevel Examination of Role Clarity - Kauppila, Olli‐Pekka (Journal of Management Studies, 2014)
AbstractAlthough prior research generally holds that role clarity is affected by both individual characteristics and organizational contexts, current conceptual or empirical models do not reflect the multilevel nature of these antecedents. A more complete understanding of how role clarity emanates from different organizational levels is necessary to help prevent poor job performance and other harmful consequences of ambiguous role expectations. To address this, I begin this research by investigating the effects of internal work locus of control, general self‐efficacy, and leader–member exchange on role clarity. With respect to the cross‐level effects, I focus on the roles of a manager's control style and the organization's strategy‐making pattern. Analyses of a multi‐industry, multilevel dataset collected from 724 employees and 124 managers in 25 organizations in Finland suggest that all of the individual‐level independent variables and a deliberate strategy‐making pattern improve role clarity. However, a deliberate strategy‐making pattern negatively moderates the relationship between general self‐efficacy and role clarity. Finally, even though an outcome‐based control system causes role ambiguity among employees in most functional areas, it may be an effective driver of role clarity among employees in sales jobs.